Diversity and multipurpose utility of wild edible plant in Chopta –Mandal forest, Uttarakhand: Life Sciences-Botany for Better Health and Nutrition - Agarwal, Reenu; Chandra, Veena (International Journal of Life Science and Pharma Research, 2021)
Wild edible plants (WEP) play a very important role in providing stable and supplemented food and also the source of income to local communities providing food security during lean periods. The present study was conducted in 11 villages covering the Chamoli and Rudraprag district of Uttarakhand. The information was collected through structured questionnaires along with field visit, group discussions and key informant interviews. The methods employed in the study is designed with the purpose of providing baseline information on the ethnobotanical use of plant species in local communities. The study recorded 64 species of WEP belonging to 47 genera and 36 families. Most of the species are used as fruits (30 species) followed by leafy vegetables (20), about 31 wild edibles plant species are used as medicinal and almost half of the species (51%) were also used for purposes other than food and 28% species with market value. A few wild edible species are used for making pickles, chutney, jam, jelly and squash through value addition to ensure high returns in comparison to selling of raw materials. Dependency of local people on the wild edible plants for economic potential is still alive and is a traditional culinary practice that demonstrates rich traditional knowledge of local people. Wild edible plants provide all the essential nutrient and minerals to the local inhabitants to stay healthy but unfortunately the traditional knowledge on the use of WEP is diminishing. WEP are not only important for livelihood but have a great potential for crop improvement. These wild species should be promoted for income generation activities through sustainable collection and trade as they are important throughout the year because their consumption serves multiple purposes.